Immunohistochemical Expression of SOX-10 in Spindle Cell Neoplasms - Gupta, Sumiti; Savan, Ajadiya; Rathee, Pooja; Gupta, Nishtha; Marwah, Nisha; Singh, Sunita (Annals of Pathology and Laboratory Medicine, 2025)
Background: Spindle cell neoplasms may range from benign to malignant tumors. This heterogenous group of lesions includes those of neural, fibroblastic, myofibroblastic, myogenic, epithelial and vascular tumors. This study was conducted to evaluate the immunohistochemical expression of SOX-10 in spindle cell neoplasms. Materials and Methods: The study comprised of total 50 cases of spindle cell neoplasm collected over a period of one year and evaluated for SOX-10 expression using the immunohistochemistry technique. Results: Out of 50 cases of spindle cell neoplasms, 44% were benign and 56% were malignant. Patients age ranged from 17 to 89 years with female predominance (male:female::2:3). Tumor size in maximum dimension varied from 0.3 to 15 cm with a mean diameter of 4.8 cm. SOX-10 positive immunohistochemical expression was seen in 38.0% cases. Nuclear staining of SOX-10 was evaluated according to the four-point system of Adams et al. SOX-10 expression was significantly associated with tissue/site, S100, SMA and benign spindle cell neoplasms, while no statistically significant association was seen with malignant spindle cell neoplasms. Conclusion: The present study on spindle cell neoplasms highlights the importance of accurate diagnosis in guiding appropriate treatment.